The Congregation's Perception of the Role of the Pastor as a Christian Religious Education Teacher - Alexsander (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research stems from concerns about the lack of pastoral roles in Sunday school teaching. Shepherds only focus on serving adults and youth. This study aims to identify and explain the forms of CE and the mechanism of its implementation in the congregation. And the author wants to know the role of the pastor as a CE teacher. This research uses the descriptive qualitative method. This study indicates that there are CE forums in the local congregation, including Sunday school forums, youth forums, men's forums, women's forums, rayon forums, and public worship forums. Activities in these CRE forums are carried out at certain times according to the management of each congregation. The role of the pastor in each of these institutions is generally applied to a task delegation system for each CE forum administrator. However, in particular, the Siding Pastor has not shown his active role as a CE teacher in the Sunday School, Youth Youth and Women's Forum. The role of the Shepherd is more focused on the sermon on the pulpit at the Sunday service.